2013
DOI: 10.1111/j.1477-2574.2012.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Early post‐operative prediction of morbidity and mortality after a major liver resection for colorectal metastases

Abstract: Biochemical analyses of blood on POD1 enables stratification of patients into low- and high-risk groups for negative outcomes, with serum bilirubin associated with overall and hepatic morbidity and AST associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…Therefore, peak transaminase levels seem to have clinical value despite contrasting previous reports. 16,22 In addition, peak AST level was also an independent predictor of postoperative morbidity in the present study, despite a poor positive predictive value of peak AST and ALT for morbidity. AST was more predictive of outcomes compared to ALT, however not significant.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, peak transaminase levels seem to have clinical value despite contrasting previous reports. 16,22 In addition, peak AST level was also an independent predictor of postoperative morbidity in the present study, despite a poor positive predictive value of peak AST and ALT for morbidity. AST was more predictive of outcomes compared to ALT, however not significant.…”
Section: Discussionmentioning
confidence: 64%
“…[19][20][21] These could all contribute to the contrasting results in several reports on the predictive value of peak ALT and AST. 16,22 In the present study, postoperative peak ALT and AST levels showed a good discriminative value for postoperative mortality, especially in major liver resections and resections for PHC. Furthermore, the optimal cut-off value for peak AST levels was an independent predictor of 90-day mortality along with major morbidity and age.…”
Section: Discussionmentioning
confidence: 83%
“…Leczenie chirurgiczne przerzutów do wątroby jest bezpieczne w wyspecjalizowanych ośrodkach. Wyniki wczesne (śmiertelność pooperacyjna, odsetek powikłań) uzyskane w naszej Klinice są porównywalne do tych, jakie uzyskuje się w wyspecjalizowanych ośrodkach chirurgii wątroby (powikłania -28%; śmiertelność 90-dniowa -4,7%) [6].…”
Section: Dyskusjaunclassified
“…At the same time, there is not one liver test that reflects all components of the diverse spectrum of liver function . Two papers in this issue of HPB deal with the prediction of post‐hepatectomy liver failure (PHLF), a dramatic event that is difficult to manage as effective substitution of liver function by means of liver assist devices including the bioartificial liver, is still lacking. PHLF should be the equation of failure to predict accurately liver functional reserve pre‐operatively, given the extent of the resection considered necessary to remove all of the tumour and the quality of liver parenchyma.…”
mentioning
confidence: 99%
“…In both papers, from Leeds and Warsaw, PHLF prediction is based on serum liver function tests (LFTs). The term LFT is confusing in the present context as these parameters do not all reflect liver function.…”
mentioning
confidence: 99%